Use of Trichoderma culture filtrates as a sustainable approach to mitigate early blight disease of tomato and their influence on plant biomarkers and antioxidants production - Imran, Muhammad; Abo-Elyousr, Kamal A. M.; Mousa, Magdi A. A.; Saad, Maged M. (Frontiers in Plant Science, 2023)
Introduction Alternaria solani is a challenging pathogen in the tomato crop globally. Chemical control is a rapid approach, but emerging fungicide resistance has become a severe threat. The present study investigates the use of culture filtrates (CFs) of three species of Trichoderma spp. to control this disease. Methods Highly virulent A. solani strain and three Trichoderma fungal strains viz., T. harzianum (Accession No: MW590687), T. atroviride (Accession No: MW590689) and T. longibrachiatum (Accession No: MW590688) previously isolated by authors were used in this study. The efficacy of culture filtrates (CFs) to mitigate early blight disease were tested under greenhouse and field conditions, experiments were conducted in different seasons of 2020 using a tomato variety “doucen”. Results and discussion The CFs of T. harzianum, T. longibrachiatum, and T. atroviride significantly inhibited the in vitro mycelial growth of A. solani (62.5%, 48.73%, and 57.82%, respectively, followed by control 100%). In the GC–MS analysis of Trichoderma CF volatile compounds viz., harzianic acid (61.86%) in T. harzianum, linoleic acid (70.02%) in T. atroviride, and hydroxymethylfurfural (68.08%) in the CFs of T. longibrachiatum, were abundantly present. Foliar application of CFs in the greenhouse considerably reduced the disease severity (%) in all treatments, viz., T. harzianum (18.03%), T. longibrachiatum (31.91%), and T. atroviride (23.33%), followed by infected control (86.91%), and positively affected the plant biomarkers. In the greenhouse, the plants treated with CFs demonstrated higher flavonoids after 6 days of inoculation, whereas phenolic compounds increased after 2 days. The CF-treated plants demonstrated higher antioxidant enzymes, i.e., phenylalanine ammonia-lyase (PAL) and peroxidase (POD), after 4 days, whereas polyphenol oxidase (PPO) was higher after 6 days of inoculation, followed by healthy and infected controls. In open field conditions, disease severity in CF-treated plants was reduced in both seasons as compared to naturally infected plants, whereas CF-treated plants exhibited a higher fruit yield than controls. The present results conclude that CFs can be a potential biocontrol candidate and a promising alternative to the early blight pathogen for sustainable production.